Guidelines for developing a healthy prison and preparedness before inmates in correctional institutions towards sustainable development in Thailand - Chotpittayanon, Natnicha (Kasetsart Journal of Social Sciences, 2026)
This research article explores the development of healthy prisons and the preparation of female inmates for sustainable reintegration into society. The study aims to assess the historical, theoretical, and practical aspects of healthy prison environments, focusing on the current conditions and challenges faced by female inmates. Using a qualitative research approach, data were collected from 24 key informants, including female prison administrators and staff. The study identifies significant barriers such as overcrowding, outdated facilities, and inadequate healthcare, which adversely affect inmates’ physical and mental well-being. Overcrowding, driven by rising inmate populations, contributes to stress, health issues, and limited activity space, while insufficient medical personnel and facilities further constrain health care delivery. Additionally, the study highlights barriers in preparing female inmates for release, including educational deficits, inadequate vocational training, and limited access to essential resources. Educational programs often fail to align with inmates’ interests or market needs, and vocational training is hampered by financial and logistical constraints. Moral and spiritual development is also challenged by psychological issues and limited support networks. To address these challenges, the study recommends a multifaceted approach that includes enhancing prison infrastructure, improving educational and vocational programs, and supporting mental and emotional well-being through family and community involvement. Effective prison reform requires collaboration among relevant agencies to ensure that female inmates are successfully reintegrated into society and can achieve long-term sustainability.